Humour et Figures de l’engagement. Le cas de Ronny Coutteure - Yannick Lebtahi (Mise au Point)
Ronny Coutteure reached the top of his fame on TV, in movies and on stage through the 1980s and 1990s. Ronny was an artist, actor, singer, storyteller, entertainer and show host, director and filmmaker. Starting his career as what Dominique Noguez calls “L’arc-en-ciel des humours” (meaning: “the rainbow of humors”), he progressively moved towards a more universal type of humour, eventually pleasing a more diverse audience. The diversity of Ronny Coutteure’s audience shows the plural identity of the Nord/Pas-de-Calais region. It also shows that laugh is a real identity maker throughout cultures. In the 1960s the Nord/Pas-de-Calais regional TV actually used humour as a tool to foster a cultural and artistic orientation to its programming. But once institutionalized, the local TV progressively abandoned the regional actors who embodied the identity of the region. Digging into Ronny Coutteure’s archives is a way to discover the key features of his humour, which reinforced the social fabric of the region Nord Pas-de-Calais. The retrospective not only shows how Coutteure’s humour played a key role in his personal life, it also makes it obvious that it is part of our collective memory and remains relevant to date.